(untitled) (Dhaka University Journal of Linguistics, 2011)
Kok-Borok is the native language of the Borok people in the Indian state of Tripura and its neighbouring areas of Bangladesh. The aim of the present study is to capture the typological analysis of causative constructions of Kok-Borok, a language which belongs to the Bodo sub-group of the Tibeto-Burman language family. Our study shows that the most remarkable aspect of the causative constructions in Kok-borok is that in double causatives, the causative rI ’give’ has been reduplicated in order to express ’to make somebody to do by employing a third party’, which shows the language Kok-Borok’s unique features if we compare this language with the other South-Asian Tibeto-Burman languages. The findings of mixed causatives show that both periphrastic and morphological devices have been employed in Kok-Borok to convey the meaning of causative constructions. Key Words: Causatives; Lexical; Morphological or Periphrastic Causatives; Kok-Borok. DOI: 10.3329/dujl.v2i4.6902 Dhaka University Journal of Linguistics Vol.2(4) August 2009 pp.115-137